KINERJA APARATUR SIPIL NEGARA (ASN) DALAM MENINGKATKAN KUALITAS PELAYANAN PADA DINAS PENDIDIKAN KABUPATEN LAMPUNG SELATAN - Malik Malik (e-JKPP, 2019)
Performance of Public Servant Civil of In Improving Service Quality of On Duty Education of National of Young Fellow And Athletics of Regency Lampumg Selatan.this Research Target is to know and analyse : (1) To know and analyse the Performance of Public Servant of Civil At On Duty Education of National of Young fellow and athletics of Regency Lampung Selatan, (2) To know and analyse the service Quality of At On Duty Education of National of Young fellow and athletics of Regency Lampumg Selatan.this Research Method is use the research type qualitative with the descriptive analysis method. this Method use is to mendeskripsikan of Performance of Public servant of civil At On Duty Education of National of Young Fellow And Athletics of Regency Lampumg Selatan, studying qualitative, how All data obtained is direct the than field informan by using interview and obsevasi.Conclusion that officer performance of On Duty Education of National of Young fellow and athletics of Regency Lampumg Selatan not yet goodness, that matter because not yet been supported with the storey;level of officer education, good of formal education, and also with the education and training which have been followed by the officer. later;then officer skill which relative not yet baik, so that service not yet optimal, because not yet full supported by adequate experience because generally existing officer represent the officer which not yet old undertake at On Duty Education of National of Young fellow and athletics of Regency Lampumg Selatan although have there are some officer also which is since lifted to undertake at the office. But that way, constraint found by after following education and training, officer behave and is behavioral in work attitude which not yet as according to expectation so that can lessen the officer performance, in giving service.